2021
DOI: 10.1155/2021/5560891
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Hydroxyapatite-Based Bone Scaffold with Gentamicin Accelerates Vascularization and Remodeling of Bone Defect

Abstract: Osteomyelitis is an infectious disease which is also a major complication of bone defects. This study aims to determine the effect of bovine hydroxyapatite-gelatin-based bone implants with gentamicin as an antibiotic (BHA-GEL-GEN implant) on the regeneration of bone defects in vivo. The BHA-GEL-GEN and BHA-GEL implants were made by direct compression. In vivo study was carried out with Wistar rats. The rats were divided into three groups: negative control, BHA-GEL implant, and BHA-GEL-GEN implants. The defect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Microscale-sized HA (microHA) is the classical HA used as bone tissue scaffold. The administration of microHA was able to induce new bone growth in the defect area in vivo [9,47]. However, Chandran et al (2016) showed that the administration of microHA in osteoporotic rats did not provide a higher regeneration efficiency than the sham group [48].…”
Section: Hamentioning
confidence: 96%
See 3 more Smart Citations
“…Microscale-sized HA (microHA) is the classical HA used as bone tissue scaffold. The administration of microHA was able to induce new bone growth in the defect area in vivo [9,47]. However, Chandran et al (2016) showed that the administration of microHA in osteoporotic rats did not provide a higher regeneration efficiency than the sham group [48].…”
Section: Hamentioning
confidence: 96%
“…HA (Ca 10 [PO 4 ] 6 [OH] 2 ) is a derivate of calcium phosphate along with tricalcium phosphate and bioglass ceramic [29]. Calcium phosphate is often used as a biomaterial for the production of bone and dental tissue implants, or as a drug delivery system targeting hard tissue [2,6,9,30]. The organic and inorganic components account for 40% and 60% of the extracellular matrix (ECM) of bone, respectively.…”
Section: Hamentioning
confidence: 99%
See 2 more Smart Citations
“…Carbonated HA was found to increase osteoblast proliferation in vitro [ 20 ]. Other characteristics of BHA, such as its high compressive strength, prevent premature degradation and support bone formation in vivo [ 16 , 21 ].…”
Section: Introductionmentioning
confidence: 99%